Xicotepec, Magical Town: Economic and Sustainable Development Perspective (GEON Journal (Management, Organizations and Business), 2021)
Problematic: The name granted to Xicotepec de Juárez as Magical Town in 2011 does not show substantive improvements for its inhabitants and businessmen in the tourism sector.Objectives: Determine strategies for economic and sustainable development in Xicotepec, a magical town. Materials and methods: Quantitative research with a non-experimental, transactional, and descriptive design. Two questionnaires, survey type, were applied to 76 businessmen and 355 citizens in the municipality of Xicotepec. Results: Mainly, it is found that citizens do not perceive the name of Magical Town, as a detonating factor of tourism and neither as an element that improves their quality of life, because 49.86% of the inhabitants consider it regular and 21.69% as bad. On the other hand, the businessmen reflect various areas of opportunity in the labor and operational spheres and also the evaluation they give to the name of Magical Town is regular with 65.79% and only 23.68% consider it good. Discussion: In general terms, it is perceived that Xicotepec, like other Magical Towns, has various problems so tourism is considered as a true trigger for local development and is a factor of benefit for both residents and businessmen. Conclusions: Xicotepec has the opportunity to generate new ways of living in its social, economic, competitive and sustainable environment. It requires networks and collaboration links that allow contributing to the commercialization of tourism opening and strengthening, which significantly impacts Xicotepec's families. Contribution/originality: The main contribution of this work has to do with the identification of the current aspects that both residents and businessmen live in and that can serve as a basis for decision-makers who implement improvement strategies.
Keywords: economy; local development; magic town; quality of life; sustainable tourism; Xicotepec